Drug utilization study of atopic dermatitis in a tertiary care hospital - Vemuri, Veena Rani; Nayak, Usha V. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Atopic dermatitis is a chronic relapsing hypersensitivity manifestation of the skin which has shown an increasing prevalence world over. It ranges from a mild atopic itch to an unrelenting chronic eczema. Its prevalence which is on the rise necessitates a rational approach to the diagnosis and treatment. Methods: A prospective study was conducted for a period of six months and 245 prescriptions were collected after obtaining requisite permission and a proper informed consent. The data was analysed by using WHO drug use indicators. Results: Of the 245 prescriptions analysed, there was a female predominance with a female to male ratio of 1.63:1. Age group presenting more with the symptoms of atopic dermatitis was 20 to 29 years. Antihistamines were the most commonly prescribed medication (221), Emollients were present in 193 prescriptions. Topical steroids were received by 150 patients of whom 51 were prescribed as an FDC. Tacrolimus was given to 17 patients. Conclusions: It is essential to rule out helminthic infestation, scabies and seborrhoea dermatitis to make a proper diagnosis of atopic dermatitis. More generic prescribing wherever possible might help to reduce the cost per patient.